Blood parameters of local Kedah-Kelantan cattle - Yusoff, Mazenah; M. Fadzil (Persatuan Doktor Veterinar Malaysia, 1985)
Haematological and biochemical parameters of Kedah-Kelantan (KK) cattle were studied. The adult KK cattle had lower mean erythrocyte count and PCv, and higher mean leucocyte counts than the temperate breeds. The protein concentrations were higher in adult animals than calves because of the increase in albumin level with age. The SGOT, BUN and creatinine values were similar to findings in other breeds. The calcium and inorganic phosphorus levels in adult KK cattle were low compared to other breeds because of the influence of nutrition and age especially on phosphorus mobiliza- tion. Alkaline phosphatase showed a similar trend as in other breeds